HUBUNGAN WORD OF MOUTH AND STORE ATMOSPHERE TERHADAP IMPULSE BUYING (STUDI PADA PASAR MODERN DARI KOREA / MINISO) - I Wayan Tirta Sinar Jaya; Ni Luh Ketut Ayu Sudha Sucandrawati; I Gusti Ayu Pradnya Paramitha (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the effect of partial and simultaneous word of mouth and store atmostphere simultaneously on impulse buying in modern stores from Korea / Miniso. The method carried out in this study is a quantitative descriptive method using the type of research with a survey method with a data collection instrument in the form of a questionnaire to obtain information about a number of respondents representing a certain population which will then be carried out statistical data analysis (SPSS) to test the hypothesis that has been proposed. The results of this study found that word of mouth and store atmosphere partially had a significant and simultaneous effect on the impulse buying of Miniso consumers. Where the double linear regression model results are as follows: Y = 2.764 + 0.171 X1 + 0.100 X2 + e. Where it can be interpreted as follows, the constant value of 2.764, means that if the variables word of mouth and store atmosphere are equal to zero, then tourist satisfaction is 2.764. For the value of the beta coefficient in the service quality variable of 0.253 which means that every change in the word of mouth variable (X1) by one unit will result in a change in impulse buying (Y) of 0.071 units. with other assumptions is fixed. While the value of the beta coefficient in the store atmosphere variable is 0.100 which means that any change in the store atmosphere variable (X2) by one unit will result in a change in impulse buying (Y) of 0.764 units with other assumptions being fixed.